The diagnosis and treatment of dermatitis herpetiformis - Antiga E; Caproni M (Clinical, Cosmetic and Investigational Dermatology, 2015)
Emiliano Antiga, Marzia Caproni Department of Surgery and Translational Medicine, Section of Dermatology, University of Florence, Florence, Italy Abstract: Dermatitis herpetiformis (DH) is an inflammatory cutaneous disease with a chronic relapsing course, pruritic polymorphic lesions, and typical histopathological and immunopathological findings. According to several evidences, DH is considered the specific cutaneous manifestation of celiac disease, and the most recent guidelines of celiac disease have stated that, in celiac patients with a proven DH, a duodenal biopsy is unnecessary for the diagnosis. In this review, the most recent data about the diagnosis and the management of DH have been reported and discussed. In particular, in patients with clinical and/or histopathological findings suggestive for DH, the finding of granular IgA deposits along the dermal–epidermal junction or at the papillary tips by direct immunofluorescence (DIF) assay, together with positive results for anti-tissue transglutaminase antibody testing, allows the diagnosis. Thereafter, a gluten-free diet should be started in association with drugs, such as dapsone, that are able to control the skin manifestations during the first phases of the diet. In conclusion, although DH is a rare autoimmune disease with specific immunopathological alterations at the skin level, its importance goes beyond the skin itself and may have a big impact on the general health status and the quality of life of the patients. Keywords: dermatitis herpetiformis, celiac disease, diagnosis, treatment, autoimmune disease, inflammatory cutaneous disease